Edukasi Dan Pendampingan Pemanfaatan Teknologi Tepat Guna Melalui Smart Filter Air Sumur Bor Kawasan Perumnas Sijambi Kota Tanjungbalai - Ruri Prihatini Lubis; Yenni Ramadhani Harahap; Riska Franita (Cattleya Darmaya Fortuna, 2025)
The Directorate General of Water Resources of the Ministry of Public Works and Public Housing (2014) stated that the problem of scarcity and unequal access to clean water in Indonesia is caused by increasing water demand, such as population growth, increased agricultural, industrial, mining, hotel activities, and the expansion of residential areas [1]. The clean water crisis and scarcity are also occurring in Tanjungbalai City. The President Director of PDAM Tirta Kualo invited the Director of UNESCO Asia Pacific, Prof. Shahbaz Khan, to conduct research on the crisis and poor water quality in Tanjungbalai City. One area of ​​Tanjungbalai City that is urgently affected by the scarcity and unequal access to clean water is the community of housewives in Perumnas Sijambi, Tanjungbalai City. The Perumnas Sijambi housewives social group became partners in this community service activity. These partners are customers of PDAM Tirta Kualo, whose service utilizes drilled well water as a source of clean water, although the water quality is not suitable for drinking. The main problems that are obstacles to the business of the Sijambi Housewives Group partners in Tanjung Balai City are 1) Production Aspects, because the income level of partners is still very low and the local PDAM has not fulfilled the provision of clean water to customers, resulting in the quality of water production; 2) Social Aspects of the Community, the Health Condition of the partners' drilled well water is in an unhealthy condition and is not suitable for drinking. The solution provided by the community service team to overcome the business obstacles mentioned above by designing and making a PILOT PROJECT of Appropriate Technology Tools (TTG)